The efficacy of captopril and 5-fluorouracil combination in the proliferation and collagen deposition of keloid fibroblast - Jesslyn Amelia; Yohanes Widodo Wirohadidjojo; Agnes Sri Siswati (Indonesian Journal of Biotechnology, 2022)
Keloid is a benign fibroproliferative tissue growth that exceeds the initial wound margins. Captopril has been tested in vitro to reduce fibroblast proliferation and collagen deposition; thus, it has potential for use in the treatment of keloids. Meanwhile, 5‐fluorouracil (5‐FU) has already been used in keloid management. This study aimed to determine the efficacy of the combination of captopril and 5‐FU in keloid fibroblast cultures. Keloid tissues were cultured up to passages 4–7. The study consisted of a control group, captopril in various concentrations (10‐2, 10‐3, 10‐4, and 10‐5 mol/L), 5‐FU 1 mg/mL and a combination of captopril at various concentrations with 5‐FU 1 mg/mL. After 144 hours of treatment, fibroblast proliferation and collagen deposition were measured. The study showed a significant decrease in the mean index of fibroblast proliferation and collagen deposition in the group receiving captopril in various concentrations (10‐2, 10‐3, 10‐4, and 10‐5 mol/L) and the 5‐FU group against the control group (p<0.05). In the combined‐dose group, captopril at a concentration of 10‐2 mol/L and 5‐FU showed a significant reduction in fibroblast proliferation and collagen deposition compared to the 5‐FU group and the captopril at the same dose (p<0.05). In conclusion, the combination of captopril 10‐2 mol/L and 5‐FU 1 mg/mL is better at reducing fibroblast proliferation and collagen deposition in keloid fibroblast cultures than captopril or 5‐FU as a single therapeutic agent.